Pemetaan Lokasi Pembuangan Sampah Ilegal Menggunakan Sistem Informasi Geografis (SIG) di Tujuh Wilayah Kecamatan Kota Yogyakarta - Widiatmoko, Alan; Putra, Hijrah Purnama; Wacano, Dhandhun (Universitas Riau, 2025)
Population growth of Yogyakarta City is increasing due to birth and immigrant numbers coming from outside the region. This can affect the amount of waste generated as of garbage disposal must be sufficient to accommodate lots of wastes. The purpose of this research is to identify and mapping the point of ilegal dumping locations, analyze policy on waste management and factor the cause of the emergence ilegal dumping. This research is using census method which is direct research location using Garmin 60CSx type GPS device. Then mapped using the GIS software ArcMap 10.4.1. The research are located in seven districts in Yogyakarta City, there are Gondokusuman, Pakualaman, Danurejan, Gondomanan, Mergangsan, Umbulharjo and Kotagede Subdistricts. The results showed that found 33 locations of ilegal dumping in seven research areas. The three factors causing the emergence of ilegal dumping are geophysical, anthropogenic, and population density each have an influence on the emergence of ilegal dumping but not too significant. Based on analysis of the technical regulations for the implementation temporary garbage dumps, 33 ilegal dumping were found does not eligible technical requirements for the implementation of temporary garbage disposal, and the existing regional regulations are considered implemented properly because still many ilegal dumping are found